Sequences of acetyl CoA carboxylase promoter for tumour necrosis factor action - Keerang Park; Michael E. Pape; Ki-Han Kim (Mediators of Inflammation)
Tumour necrosis factor (TNF) inhibits the accumulation of acetyl CoA carboxylase (ACC) mRNA by decreasing the rate of ACC gene transcription. The ACC mRNA species found in 30A5 cells are generated from promoter II and TNF inhibits the accumulation of class 2 type mRNAs. By using 5' deletion mutants of promoter II fused to the bacterial chloramphenicol acetyltransferase (CAT) gene, the DNA mobility shift assay and the DNase I footprinting assay, the authors have identified the 30 bp from −389 to −359 as the TNF responsive element in promoter II. TNF treatment causes a decrease in the binding activity of nuclear protein(s) specific to the TNF responsive element. When the fragment containing the TNF responsive element was incorporated into the thymidine kinase promoter, the chimeric gene exhibited TNF induced inhibition of expression.